Concentrations of oligomers and polymers of proanthocyanidins in red and purple rice bran and their relationships to total phenolics, flavonoids, antioxidant capacity and whole grain color. (1st October 2016) - Chen, Ming-Hsuan; McClung, Anna M.; Bergman, Christine J.
Highlights: A 4.3-fold variation in total proanthocyanidins found among 32 red and purple brans. Proanthocyanidins ranged from monomers to 14-mers and polymers. Proanthocyanidins positively correlated with phenolics, flavonoids and ORAC values. Extractable proanthocyanidins negatively correlated with whole grain rice red color. Abstract: Proanthocyanidins, a flavonoids subgroup, are proposed to have chronic disease modulation properties. With the eventual goal of enhancing rice phytonutrient concentrations, we investigated the genotypic variation of the concentrations of individual oligomers and polymers of proanthocyanidins in red and purple rice brans. A 4.3-fold variation in total proanthocyanidins (sum of oligomers and polymers) in the extractable fraction was found and the concentration was highly correlated with total phenolics, total flavonoids and antiradical capacity. Variation in the proportion of oligomers and polymers existed, with monomers to trimers, 4–6mers, 7–10mers and polymers accounting for 7, 18, 26.5 and 48.7%, respectively, of the total. The redness value a ∗ of whole grain rice measured in CIE L ∗ a ∗ b ∗ color space was negatively and positively correlated with extractable and non-extractable proanthocyanidins, respectively. The variation found indicates it is possible to select rice with bran containing high levels of total proanthocyanidins and specific degree of polymerization profiles.